Can someone answer these questions please <3
(W+4)(w+2) =
(Y+1)(y+2) =
(C+2)(c+5) =
(A+5)(a-5) =
(G+7)(g-4) =
(S-4)(s+5 =
(2c+1)(2c+3)
(5x+1)(2x+5)
(3w+2)(w+1)
(3w+2)(w+1)
(3p+2)(2p-1)
(6g-4)(g+1)

I will award brainliest answer please don’t fake the answers I’m failing enough already :/

Respuesta :

Step-by-step explanation:

For double brackets algebraic, every term in the first bracket must be multiplied by every term in the second bracket. You need to expand the brackets first, so your first question (w+4)(w+2) will be layed out like this:

w(w+2) + 4(w+2).

You must now multiply (x) the terms inside each bracket by the terms outside each bracket =

w(w+2) + 4(w+2) = w² + 2w + 4w + 8.

The last step is to simplify. With w² + 2w + 4w + 8, you are adding together the two middle w terms. 2w + 4w = 6w.

Therefore the answer will be = w² + 6w + 8 to Q1.

Let's try another, further down in the list.

With (3w+2)(w+1), expanding the brackets will look like this:

3w(w+1) + 2(w+1).

Now we will multiply what is inside the bracket by what is outside the bracket=

3w(w+1) + 2(w+1) = 3w² + 3w + 2w + 2.

Now we will simplify the middle like terms.

3w + 2w = 5w.

Therefore the answer will be: 3w² + 5w + 2.

I have sent you the answer to one so you can understand it. Hope it helps..
Ver imagen areebarehmanb
ACCESS MORE